Dual-procedural separation of CTCs in cutaneous melanoma provides useful information for both molecular diagnosis and prognosis. (March 2020) - Tucci, Marco; D'Oronzo, Stella; Mannavola, Francesco; Felici, Claudia; Lovero, Domenica; Cafforio, Paola; Palmirotta, Raffaele; Silvestris, Franco
Background: Circulating tumor cells (CTCs) have recently emerged as a new dynamic soluble marker for several malignancies including cutaneous melanoma (CM) and are suitable for prognostic evaluations and treatment monitoring. However, to date many limitations still hamper the wide-scale application of CTCs in CM setting, including the lack of standardized methods as well as both low levels and heterogeneity of these cells. Methods: We developed a protocol for CTC detection in CM based on immune-magnetic sorting to deplete CD45-, CD31- or CD34-positive cells, followed by dielectrophoretic DEPArray separation according to cell morphology and immunophenotype. To this end, we explored the expression of melanoma stem cell antigens (CD271, ABCB5, and RANK) and the epithelial-to-mesenchymal transition markers (N-Cad, -CD44, and -MCAM/CD146) on CTCs from 17 stage IV CM patients, and investigated their BRAF mutational status by droplet digital PCR. Results: The number of CTCs isolated from CM patients ranged from 2 to 91 cells (38 ± 6.4) with respect to healthy donors ( p < 0.0002). To confirm the melanoma origin of isolated cells, we observed an 80% agreement between their BRAF V600 mutational status and matched primary tumors. The characterization of the immune phenotype of isolated cells revealed high interindividual and intraindividual heterogeneity that was found to correlate with the clinical outcome. Conclusions: The dual-step protocol of immune-magnetic sorting and subsequent dielectrophoretic DEPArray separation, turned out to be a suitable method to isolate viable CTCs from stage IV melanoma patients and enabled quantitative and qualitative analyses on these cells, which may deserve prospective evaluation for potential use in the clinical practice.